Acute Phase Reaction Following Intravenous Administration of Streptokinase - Spöttl, F; Kaiser, R; Mosuni, M. S (Thrombosis and Haemostasis, 1974)
SK-therapy regularly is followed by a marked elevation of those plasma proteins known as “acute phase reactants” (α 1-antitrypsin, orosomucoid, β 1 C-globulin, ceruloplasmin). In short-time therapy of myocardial infarction also a transitory presence of CRP is demonstrable. After an initial decrease of fibrinogen caused by fibrinogenolysis, this protein increases significantly too. The high level of α 1-antitrypsin (slow reacting antiplasmin) and/or fibrinogen may lead to rheological consequences which may result in thrombosis.